Effect of Exposure Time and Ratio of Hosts to Female Parasitoids on Offspring Production of Diachasmimorpha longicaudata (Hymneoptera: Braconidae) Reared on Anastrepha fraterculus (Diptera: Tephritidae) Larvae - Van Nieuwenhove, Guido Alejandro (2012)
Diachasmimorpha longicaudata (Ashmead) is a larval-prepupal endoparasitoid of tephritid fruit .y pests in tropical and subtropical countries. Because citrus-growing areas of northern Argentina are the most affected by Anastrepha fraterculus (Wiedemann), D. longicaudata presents as a potential candidate for augmentative releases against it. Within this context, parasitoid rearing must be focused on offspring yield optimization in order to sustain a successful massrearing process. Hence, the best ratio of A. fraterculus larva to female parasitoids and the best exposure time for achieving the greatest parasitoid yield with the highest proportion of female progeny were determined under laboratory conditions in the present study. The effect of superparasitism on the percentage of D. longicaudata emergence was also assessed. Third-instars of A. fraterculus were exposed for 30, 60, 90, and 120 min to 30 mated, 5-7 d-old parasitoid females at host/parasitoid ratios of 2:1, 4:1, 6:1, 8:1, and 10:1. Results showed that a low ratio of hosts exposed to parasitoids for a short time was essential to achieve parasitoid emergence rates exceeding 70%, and to achieve a female:male sex ratio of at least 61:39. Increasing both the ratio of host larvae to parasitoid further than 4:1 and the exposure time of D. longicaudata to hosts beyond 30 min did not signi.cantly enhance overall parasitoid progeny yield. There was a significant negative correlation between the number of parasitoid 1st instars recorded per dissected host pupa and the percentage of parasitoid emergence. Conversely, a signi.cant positive correlation was found between superparsitism and additional host mortality. Although a female-biased sex ratio resulted in all treatments, the greater parasitoid female progeny proportions were found in association with the higher levels of superparasitism.